Conductive particles, production method therefor, and conductive material
Patent Information
- Application Number
- JP2022134210
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-08-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-08-25
AI Technical Summary
Conductive particles used in anisotropic conductive materials face challenges in achieving low connection resistance, suppressing short circuits, and ensuring high connection reliability as electronic devices continue to miniaturize and refine.
The conductive particles are designed with a core particle and a conductive layer having a plurality of protrusions, where the height variation of the protrusions is controlled within a specific range (0.01 to 0.25) to enhance uniform contact and prevent short circuits.
The solution results in conductive particles with reduced connection resistance, excellent insulation properties, and improved connection reliability, effectively addressing the challenges of miniaturization and refinement in electronic devices.
Smart Images

Figure 00000000_0001_ABST 
Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive particle, a method for producing the same, and a conductive material containing the conductive particle. [Background technology]
[0002] Conductive particles used as a conductive material for anisotropic conductive materials such as anisotropic conductive films and anisotropic conductive pastes are generally known to have a conductive layer made of metal formed on the surface of a core particle. In recent years, in connection between electrode terminals with fine pitches associated with the miniaturization and refinement of electronic devices, the conductive layer of the conductive particles provides electrical connection between electrodes and wiring.
[0003] As the conductive layer of the conductive particles, a film formed on the surface of the core particles by electroless plating of a metal such as nickel is often used, and various ideas have been devised to develop the desired characteristics. As an example, Patent Document 1 describes that by forming a plurality of polygonal columnar protrusions on the conductive layer of the conductive particles, when the conductive particles are used for electrical connection between electrodes, the conductive particles can be efficiently arranged on the electrodes and damage to the electrodes by the conductive particles can be suppressed. Furthermore, Patent Document 2 proposes a conductive particle that can efficiently reduce the connection resistance after connection even when the electrodes are connected at low voltage by forming a plurality of polyhedral protrusions, which are not polygonal columnar, on the conductive layer of the conductive particles. Furthermore, Patent Document 3 describes a conductive particle that has a plurality of protrusions on the conductive layer of the conductive particle, and at least a portion of the plurality of protrusions is formed as a plate-shaped protrusion, so that the conductive particles are unlikely to flow excessively when the electrodes are connected, and the reliability of conduction and insulation can be improved.
[0004] The above-mentioned Patent Documents 1 to 3 all attempt to solve the problem by designing the shape of the protrusions formed on the conductive layer in accordance with the desired effect. Conductive particles imparted with desired properties by varying the shape of the protrusions in this way are being studied. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-149277 A [Patent Document 2] JP 2016-119302 A [Patent Document 3] JP 2017-212033 A Summary of the Invention [Problem to be solved by the invention]
[0006] By using conductive particles having a conductive layer with protrusions formed on the surface of a core particle, the contact efficiency between the conductive particles is increased, making it possible to reduce the amount of conductive particles. Also, when an oxide film exists on the electrode surface, the oxide film can be broken by the protrusions, allowing electrical conduction and suppressing electrical resistance. It is believed that providing the conductive layer with protrusions in this manner makes it possible to lower the connection resistance when connecting electrodes and to increase the reliability of electrical continuity.
[0007] However, with the demand for further miniaturization and precision in electronic devices, there is a demand for preventing short circuits at insulating points in addition to further reducing the connection resistance of conventional conductive particles having protrusions.
[0008] Therefore, an object of the present invention is to provide a conductive particle having a low connection resistance, excellent insulation, and excellent connection reliability with suppressed short circuiting. Another object of the present invention is to provide a method for producing a conductive particle having a low connection resistance, excellent insulation, suppressed short circuiting, and excellent connection reliability. [Means for solving the problem]
[0009] In order to solve the above problems, the inventors conducted extensive research into the protrusions of conductive particles and discovered that conductive particles in which the variation in the height of the protrusions is controlled within a certain range have low connection resistance and suppress short circuits, thereby completing the present invention.
[0010] That is, the present invention provides a conductive particle having a core particle and a conductive layer having a plurality of protrusions on the surface of the core particle, the protrusions having a height variation of 0.01 or more and 0.25 or less.
[0011] The present invention also provides A step of forming a conductive layer on the surface of the core particles; forming a protrusion on the conductive layer so as to protrude from the surface; and A step of leveling the height of the protrusions The present invention provides a method for producing conductive particles having the above structure. Effect of the Invention
[0012] According to the present invention, there is provided a conductive particle having excellent connection reliability with suppressed short circuiting due to its small connection resistance and excellent insulation. Also, according to the present invention, there is provided a method for producing a conductive particle having excellent connection reliability with suppressed short circuiting due to its small connection resistance and excellent insulation. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a conceptual diagram of a conductive particle having protrusions. [Diagram 2] 2 is a SEM photograph of the conductive particles obtained in Example 1. [Diagram 3] 1 is a SEM photograph of the conductive particles obtained in Example 3. [Figure 4] 1 is a SEM photograph of the conductive particles obtained in Example 4. [Diagram 5] 4 is a SEM photograph of the conductive particles obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described below based on its preferred embodiments. The conductive particle of the present invention (hereinafter, also referred to as "the conductive particle") has a core particle and a conductive layer having a plurality of protrusions on the surface of the core particle, and the variation in height of the protrusions is 0.01 to 0.25. If the height of the protrusions of the conductive particles varies widely, it is believed that the contact between the conductive particles and the electrodes will be uneven, which will increase the connection resistance. Furthermore, if the height of the protrusions varies widely, it may cause unexpected electrical conduction and short circuits. It is believed that the conductive particles have height variations controlled within a certain range, which results in low connection resistance, suppresses short circuits, and improves connection reliability.
[0015] The core particles of the conductive particles (hereinafter also referred to as "core particles") may be in the form of particles, and may be made of either inorganic or organic materials. Examples of inorganic materials include metal particles such as gold, silver, copper, nickel, palladium, solder, etc., alloys of these metals, glass, ceramic, silica, metal or nonmetal oxides or hydrates thereof, metal silicates such as aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides, and carbon. On the other hand, examples of organic substances include thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylic acid ester, polyacrylonitrile, polyacetal, ionomer, and polyester, and thermosetting resins such as alkyd resins, phenolic resins, urea resins, benzoguanamine resins, melamine resins, xylene resins, silicone resins, epoxy resins, and diallyl phthalate resins. These may be used alone or in combination of two or more.
[0016] The material of the core particle may be either one of the above-mentioned inorganic and organic materials, or both inorganic and organic materials.When the core particle is made of both inorganic and organic materials, the existence mode of the inorganic and organic materials in the core particle may be, for example, a core made of inorganic material and a shell made of organic material covering the surface of the core, or a core-shell type configuration such as a core made of organic material and a shell made of inorganic material covering the surface of the core.Other than these, a configuration in which inorganic and organic materials are mixed in one core particle, or a blend type configuration in which they are randomly fused, may be mentioned.
[0017] The core particles are preferably made of a material containing an organic substance, and more preferably made of a material consisting of both inorganic and organic substances. When made of a material consisting of both inorganic and organic substances, the inorganic substances are preferably glass, ceramic, silica, metal or nonmetal oxides or their hydrates, metal silicates such as aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides, and carbon. The organic substances are preferably natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylic esters, polyacrylonitrile, polyacetal, ionomers, polyesters, and other thermoplastic resins. By using a core material consisting of such a material, the dispersion stability of the particles can be increased, and when electrically connecting electronic circuits, appropriate elasticity can be expressed to increase conduction.
[0018] When the core particles are made of a material containing an organic substance, the organic substance does not have a glass transition temperature or has a glass transition temperature of more than 100° C., since the shape of the core particles is easily maintained and the shape of the core particles is easily maintained in the process of forming a metal coating. The glass transition temperature can be determined, for example, as the intersection point of the tangent of the original baseline and the inflection point in the baseline shift part of a DSC curve obtained by differential scanning calorimetry (hereinafter also referred to as "DSC").
[0019] When the organic material is a highly crosslinked resin, even if the glass transition temperature is measured up to 200°C by the above method, the baseline shift may be hardly observed. In this specification, such an organic material is also called an organic material having no glass transition temperature. The core particles may use such an organic material having no glass transition temperature as the material of the core particles. The organic material having no glass transition temperature can be obtained by copolymerizing a monomer constituting the thermoplastic resin or thermosetting resin exemplified above with a crosslinkable monomer. Examples of crosslinkable monomers include tetramethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide di(meth)acrylate, tetraethylene oxide (meth)acrylate, 1,6-hexane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimeterolpropane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, tetramethylolmethane tri(meth)acrylate, Examples of such monomers include polyfunctional (meth)acrylates such as tetramethylolmethane tetra(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol di(meth)acrylate, glycerol tridi(meth)acrylate, etc., polyfunctional vinyl monomers such as divinylbenzene and divinyltoluene, silane-containing monomers such as vinyltrimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, etc., and monomers such as triallyl isocyanurate, diallyl phthalate, diallyl acrylamide, diallyl ether, etc. In particular, in the field of COG (Chip on Glass), such highly crosslinked resins are preferably used as the material for core particles because of their hardness.
[0020] The shape of the core particles may be amorphous, spherical, fibrous, hollow, plate-like or needle-like, but is usually spherical. The core particles may have a number of protrusions on their surface. The shape of the core particles is preferably spherical from the viewpoints of excellent filling ability and ease of metal coating.
[0021] The conductive particles have a conductive layer on the surface of the core particle, and the conductive layer has a plurality of protrusions. The conductive layer of the conductive particles is made of a metal having electrical conductivity. Examples of the metal constituting the conductive layer include metals such as gold, platinum, silver, copper, iron, zinc, nickel, tin, lead, antimony, bismuth, cobalt, indium, titanium, germanium, aluminum, chromium, palladium, tungsten, molybdenum, calcium, magnesium, rhodium, sodium, iridium, beryllium, ruthenium, potassium, cadmium, osmium, lithium, rubidium, gallium, thallium, tantalum, cesium, thorium, strontium, polonium, zirconium, barium, and manganese, as well as metal compounds such as ITO and solder. Among these, gold, silver, copper, nickel, palladium, rhodium, and solder are preferred because they have low electrical resistance, and nickel, gold, palladium, nickel alloys, gold alloys, and palladium alloys are more preferred. The metal may be one type, or two or more types may be used in combination.
[0022] The conductive layer of the conductive particles may be a single layer structure or a laminated structure consisting of multiple layers. In the case of a laminated structure consisting of multiple layers, the outermost layer preferably contains at least one selected from the group consisting of nickel, gold, silver, copper, and palladium, and nickel, gold, silver, copper, palladium, and their alloys are preferred. In the case of alloys, nickel alloys, gold alloys, silver alloys, copper alloys, and palladium alloys, which are alloys of nickel, gold, silver, copper, or palladium and phosphorus, are preferred, and nickel-phosphorus alloys and palladium-phosphorus alloys are more preferred. The outermost layer of the conductive layer is more preferably an electroless nickel-phosphorus plating layer formed by an electroless method in the manufacturing method described below.
[0023] The conductive layer of the conductive particle may cover the entire surface of the core particle or only a part of it. When only a part of the surface of the core particle is covered, the covered part may be continuous or may be discontinuous, for example, in an island shape.
[0024] From the viewpoint of the electrical properties of the resulting conductive particles, the thickness of the conductive layer of the conductive particles is preferably 0.1 nm to 2,000 nm, more preferably 1 nm to 1,500 nm. The height of the protrusions of the conductive layer is not included in the thickness of the conductive layer. The thickness of the conductive layer can be measured by cutting the particle to be measured into two pieces and observing the cross section of the cut surface with a scanning electron microscope (SEM), and the thickness of the conductive layer is preferably within the above range.
[0025] The protrusions (hereinafter also referred to as "protrusions") of the conductive layer of the present conductive particles have a height variation of 0.01 or more and 0.25 or less. The height variation is the standard deviation of the height of the protrusions divided by the average height of the protrusions, and is expressed by the following formula (1). The standard deviation of the height can be calculated by the following formula (2), and the average height is the arithmetic mean value of the height of the protrusions calculated by the following formula (3). When the value of this variation is within the above range, the contact between the conductive particles and the electrodes becomes more uniform, leading to improved connection stability.
[0026] TIFF2024030952000002.tif24151
[0027] TIFF2024030952000003.tif33151
[0028] TIFF2024030952000004.tif31151
[0029] The variation in height of the projections is more preferably 0.05 to 0.20. The height of the protrusion refers to the shortest distance from the highest point of the top of the protrusion to the point where the base of the protrusion reaches the center of the conductive particle when the cross section of the conductive particle is observed under SEM. The height of all the protrusions of 20 different conductive particles observed under SEM observation is measured and substituted into each of the above formulas to obtain the variation in the height of the protrusions. When the protrusion has multiple vertices, the highest vertex is regarded as the height of the protrusion.
[0030] The average height of the protrusions of the conductive particles is preferably 20 nm to 1,000 nm, more preferably 50 nm to 800 nm. The number of protrusions per conductive particle is preferably 1 to 20,000, more preferably 5 to 5,000, depending on the particle size of the conductive particles. The length of the base of the protrusion is preferably 5 nm or more and 1,000 nm or less, and more preferably 10 nm or more and 800 nm or less.
[0031] The average height of the protrusions is calculated by determining the height of the protrusions in the same manner as above and then calculating using the above formula (3). The average length of the base of the protrusions refers to the length along the surface 6 of the lower layer of the conductive layer at the site where the protrusions are formed in (a) and (b) of Figure 1. The length of the base of the protrusions is the arithmetic mean value of the values measured for the length of all the bases of the protrusions of each of 20 different conductive particles observed by SEM observation.
[0032] The shape of the top of the protrusion is preferably substantially planar, in view of more uniform contact between the conductive particles and the electrode. Here, substantially planar includes a completely flat surface and a surface having a curved surface with a radius of curvature to be described later. For example, the completely planar surface 5 shown in FIG. 1(a) and the curved surface shown in FIG. 1(b) within the range of the radius of curvature to be described later are also included in the concept of substantially planar in this specification.
[0033] When the apex portion of the protrusion is substantially planar, the length of the apex portion is preferably 10 nm to 500 nm, more preferably 20 nm to 400 nm. The length of the substantially planar apex portion is the shortest distance connecting both ends of the apex portion in the cross section of the protrusion when the cross section of the conductive particle is observed with an SEM. For example, in Figures 1(a) and (b), the length of the straight line connecting the end 5a and the end 5b of the flat portion 5 in which the apex portion is substantially planar is the length of the apex portion. The length of the substantially planar apex portion of the protrusion is the arithmetic average value of the lengths of the apex portions of the cross sections of all the protrusions of each conductive particle measured for the cross sections of 20 different conductive particles observed by SEM observation.
[0034] The number of the protrusions varies depending on the particle diameter of the conductive particles, but from the viewpoint of the conductivity of the conductive particles, the number of protrusions is preferably 2 to 20,000 on average, more preferably 5 to 5,000 on average per conductive particle. The number of protrusions is the arithmetic average value of values measured for 20 different conductive particles observed by SEM observation.
[0035] When the apex of the protrusion is substantially flat, the radius of curvature of the apex is Ra, and the radius of curvature of the surface 6 of the lower layer of the conductive layer at the portion where the protrusion is formed is Rb. The ratio of Ra to Rb (Ra / Rb) is preferably 0.15 to 1.20, particularly 0.20 to 1.00. When the apex of the protrusion has a radius of curvature that satisfies the above range, the contact between the conductive particle and the electrode becomes more uniform, leading to improved connection stability. For example, Ra can be the radius of a circumscribing circle circumscribing the apex of the cross section of each protrusion, for example, for a cross section of a conductive particle observed by SEM observation. For example, Rb can be the radius of a circumscribing circle circumscribing the surface of the lower layer of the conductive layer, that is, the radius of the core particle.
[0036] By the height of the protrusion being within the above range, the contact between the conductive particle and the electrode becomes uniform, and when the top part of the protrusion is substantially flat, the contact with other conductive particles present in the vicinity of the conductive particle is suppressed, which is thought to lead to the prevention of short circuits. From this viewpoint, it is preferable that the total area of the top part of the protrusion per conductive particle that is substantially flat is large. That is, the ratio S2 / S1 of the total area of the top part of the protrusion to the projected area S1 of one conductive particle is preferably 0.50 or more, particularly 0.55 or more. In addition, S2 / S1 is less than 1, and from the viewpoint of confirming that a substantially flat protrusion is formed, it is preferably 0.95 or less, more preferably 0.90 or less. The projected area S1 of the conductive particle and the total area of the top part of the protrusion S2 can be measured by importing the SEM photographic image into an automatic image analyzer (manufactured by Nireco Corporation, Luzex (registered trademark) AP).
[0037] From the viewpoint of preventing short circuits, the shape of at least one of the protrusions is preferably irregular. When the protrusion is irregular, the top of the protrusion is surrounded by multiple curves with different curvatures when viewed from the opposite side to the base. When the top of the protrusion is viewed from the opposite side to the base, the top is preferably a shape other than a circle or a polygon. The number of irregularly shaped protrusions per conductive particle is more preferably 10 or more, and even more preferably 20 or more. Alternatively, the number of irregularly shaped protrusions is more preferably 90% or more, and even more preferably 95% or more, with the total number of protrusions per conductive particle being 100%.
[0038] The protrusions are preferably continuous with the conductive layer formed on the surface of the core particles. That is, the protrusions are preferably made of a metal or alloy, like the conductive layer. The term "continuous" here means that the conductive layer and the protrusions are made of the same material, and there is no part between the conductive layer and the protrusions that impairs the sense of unity, such as a seam. The strength of the protrusions is ensured by the conductive layer and the protrusions being continuous, so that the base of the protrusions is less likely to break even if pressure is applied during use of the conductive particles. It is more preferable that the protrusions are made of the same metal or alloy as the metal or alloy that constitutes the conductive layer formed on the surface of the core particle.
[0039] The average particle diameter of the conductive particles is preferably 0.1 μm or more and 50 μm or less, more preferably 1 μm or more and 30 μm or less. When the average particle diameter of the conductive particles is within the above range, it is easier to ensure conduction between the opposing electrodes without causing a short circuit in a direction different from that between the opposing electrodes. In the present invention, the average particle diameter of the conductive particles is the arithmetic average value obtained by randomly extracting 200 particles by SEM observation and measuring the particle diameter at a magnification of 10,000 times. When the conductive particles are spherical, the diameter of the conductive particles is the diameter of a circle projected onto a plane of the conductive particles, and does not include the height of the protrusions. When the conductive particles are not spherical, the particle diameter is the longest length of the line segments that cross the image of the conductive particles projected onto a plane.
[0040] The shape of the conductive particles is appropriately selected according to the shape of the core particles. The shape of the conductive particles may be the same as or different from the shape of the core particles, but from the viewpoint of manufacturing efficiency, it is preferable that both have the same shape. The shape of the conductive particles may be, for example, spherical, fibrous, hollow, plate-like, needle-like or amorphous. The shape of the conductive particles is preferably spherical from the viewpoint of excellent filling property and connectivity.
[0041] The present conductive particles can be produced, for example, by a production method including the following steps (hereinafter also referred to as "the present production method"). A step of forming a conductive layer on the surface of the core particles forming a protrusion on the conductive layer so as to protrude from the surface thereof A step of leveling the height of the protrusions
[0042] In the step of forming a conductive layer on the surface of the core particle (hereinafter also referred to as the "conductive layer forming step"), a conductive layer is formed on the surface of the core particle by any one of dry methods such as a vapor deposition method, a sputtering method, a mechanochemical method, a hybridization method, etc., or wet methods using an electrolytic plating method, an electroless plating method, etc. Also, a conductive layer may be formed on the surface of the core particle by a combination of these methods. The core particles used may be the above-mentioned core particles, and the preferred material and shape are as described above.
[0043] In the conductive layer forming step, it is preferable to form a conductive layer on the surface of the core particle by electroless plating, since it is easy to obtain conductive particles having desired particle characteristics, and it is more preferable to use electroless plating, since it is easy to obtain conductive particles having desired particle characteristics and it is easy to form protrusions, which will be described later. In particular, the conductive layer is preferably an electroless nickel alloy plating layer formed by an electroless method, and more preferably an electroless nickel-phosphorus plating layer.
[0044] The conductive layer forming step of forming a nickel-phosphorus alloy plating layer as the conductive layer will be described below. When electroless plating is used in the conductive layer forming step, the core particles preferably have a surface capable of trapping precious metal ions or are surface-modified to have the ability to trap precious metal ions. The precious metal ions are preferably palladium or silver ions. Having the ability to trap precious metal ions means that the precious metal ions can be captured as chelates or salts. For example, when an amino group, an imino group, an amido group, an imido group, a cyano group, a hydroxyl group, a nitrile group, a carboxyl group, or the like is present on the surface of the core particles, the surface of the core particles has the ability to trap precious metal ions. When the surface is modified to have the ability to trap precious metal ions, for example, the method described in JP-A-61-64882 can be used.
[0045] Core particles that have the ability to capture precious metal ions or have been surface-modified to have the ability to capture precious metal ions are used as the core particles, and the precious metal is supported on the surface. Specifically, the core particles are dispersed in a dilute acidic aqueous solution of a precious metal salt such as palladium chloride or silver nitrate. This allows the precious metal ions to be captured on the surface of the core particles. The concentration of the precious metal salt is usually 1 / m2 of the surface area of the core particles. 2 1x10 -7 From 1×10 -2 The amount of the core material particles captured with the precious metal ions is in the range of 1 mole. The core material particles with the precious metal ions captured are separated from the aqueous solution and washed with water. The core material particles are then suspended in water, and a reducing agent is added thereto to reduce the precious metal ions. This causes the precious metal to be supported on the surface of the core material particles. Examples of the reducing agent that can be used include sodium hypophosphite, sodium borohydride, potassium borohydride, dimethylamine borane, hydrazine, and formalin, and it is preferable to select one of these based on the constituent material of the desired conductive layer.
[0046] Before capturing the precious metal ions on the surface of the core particles, tin ions may be adsorbed on the particle surface and a sensitization treatment may be performed in order to increase adhesion to the precious metal. To adsorb tin ions on the particle surface, for example, the core particles having the surface modified as described above may be placed in an aqueous solution of stannous chloride and stirred for a predetermined period of time.
[0047] The thus pretreated core particles are subjected to a conductive layer forming step, whereby a conductive layer is formed on the surface of the core particles. After the conductive layer forming step, a step of forming protrusions protruding from the upper surface of the conductive layer (hereinafter also referred to as a "protrusion forming step") is carried out.
[0048] The protrusion forming step is preferably carried out subsequent to the conductive layer forming step described below. The conductive layer forming step is preferably an electroless nickel plating method in which an aqueous slurry of the core particles is mixed with an electroless nickel plating bath containing a dispersant, nickel salt, a reducing agent, a complexing agent, etc. In the conductive layer forming step by electroless nickel plating, the plating solution self-decomposes at the same time as the conductive layer is formed on the core particles. This self-decomposition occurs in the vicinity of the core particles, so that the self-decomposition product is captured on the surface of the core particles during the formation of the conductive layer, thereby generating the nuclei of the microprojections, and at the same time, the conductive layer is formed. The generated nuclei of the microprojections are used as base points to grow the protrusions in the protrusion forming step described below.
[0049] In the electroconductive layer forming process by electroless nickel plating, the core particles are preferably thoroughly dispersed in water in the range of 0.1 to 500 g / L, more preferably 1 to 300 g / L, to prepare an aqueous slurry. The dispersion operation can be carried out by normal stirring, high-speed stirring, or using a shear dispersion device such as a colloid mill or homogenizer. Ultrasonic waves may also be used in the dispersion operation. If necessary, a dispersant such as a surfactant may be added in the dispersion operation. Next, the aqueous slurry of the core particles that has been subjected to the dispersion operation is added to an electroless nickel plating solution containing nickel salt, a reducing agent, a complexing agent, and various additives, and electroless plating is carried out.
[0050] The above-mentioned dispersing agent includes, for example, a nonionic surfactant, an amphoteric surfactant and / or a water-soluble polymer. As the nonionic surfactant, polyoxyalkylene ether surfactants such as polyethylene glycol, polyoxyethylene alkyl ether, and polyoxyethylene alkyl phenyl ether can be used. As the zwitterionic surfactant, betaine-based surfactants such as alkyldimethylacetate betaine, alkyldimethylcarboxymethylacetate betaine, and alkyldimethylaminoacetate betaine can be used. As the water-soluble polymer, polyvinyl alcohol, polyvinylpyrrolidinone, hydroxyethyl cellulose, etc. can be used. These dispersants can be used alone or in combination of two or more. The amount of the dispersant used varies depending on the type, but is generally 0.5 to 30 g / L relative to the volume of the electroless nickel plating solution. In particular, it is preferable that the amount of the dispersant used is in the range of 1 to 10 g / L relative to the volume of the electroless nickel plating solution, from the viewpoint of further improving the adhesion of the conductive layer.
[0051] As the nickel salt, for example, nickel chloride, nickel sulfate, nickel acetate or the like is used, and the concentration is preferably in the range of 0.1 to 50 g / L. The reducing agent is used to reduce precious metal ions and is selected based on the constituent material of the intended conductive layer. Examples of the reducing agent include phosphorus compounds and boron compounds. When sodium hypophosphite is used as the phosphorus compound, the concentration is preferably in the range of 0.1 to 50 g / L.
[0052] The complexing agent may be a compound having a complexing effect on nickel ions, such as carboxylic acids or carboxylates, such as citric acid, hydroxyacetic acid, tartaric acid, malic acid, lactic acid, gluconic acid, or alkali metal salts or ammonium salts thereof, amino acids, such as glycine, amine acids, such as ethylenediamine and alkylamines, other ammonium, EDTA, or pyrophosphate (salts). These may be used alone or in combination of two or more. The concentration is preferably in the range of 1 to 100 g / L, more preferably 5 to 50 g / L. The preferred pH of the electroless nickel plating solution at this stage is in the range of 3 to 14. The electroless nickel plating reaction begins immediately upon addition of the aqueous slurry of core particles, and is accompanied by the evolution of hydrogen gas. The conductive layer formation process is terminated when the evolution of hydrogen gas is no longer observed. The thickness of the conductive layer can be controlled in the conductive layer forming step by adjusting the concentration, pH, etc. of the nickel salt, and if necessary, the dispersant, complexing agent, etc., and the thickness can be set within a preferred range.
[0053] Next, after the conductive layer forming step, a protrusion forming step is carried out. In the protrusion forming step, it is preferable to form the protrusions by adding a nickel salt, a reducing agent and an alkali to the electroless nickel plating solution in the conductive layer forming step by the electroless nickel plating method. The nickel salt, the reducing agent and the alkali can be added, for example, (i) using a first aqueous solution containing one of a nickel salt, a reducing agent and an alkali, and a second aqueous solution containing the remaining two, or (ii) using a first aqueous solution containing a nickel salt, a second aqueous solution containing a reducing agent, and a third aqueous solution containing an alkali; It is preferable. The aqueous solutions (i) or (ii) are added simultaneously to the electroless nickel plating solution, and the addition is continued to continue the electroless nickel plating. If the addition of each aqueous solution is interrupted, the plating reaction stops, and if it is added, the plating reaction starts again. By adjusting the amount of each aqueous solution added, the conductive layer formed can be controlled to a desired film thickness, and further, protrusions are formed starting from the cores of the microprotrusions generated on the surface of the conductive layer in the conductive layer forming step. After the addition of the aqueous solution to the electroless nickel plating solution has been completed, stirring is continued while maintaining the solution temperature for a while after the generation of hydrogen gas has completely ceased, to complete the reaction.
[0054] In the case of (i) above, it is preferable to use a first aqueous solution containing a nickel salt and a second aqueous solution containing a reducing agent and an alkali, but this combination is not limited to this. In this case, the first aqueous solution does not contain a reducing agent or an alkali, and the second aqueous solution does not contain a nickel salt. As the nickel salt and the reducing agent, those mentioned above can be used. As the alkali, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used.
[0055] In the above-mentioned case of (ii), the first to third aqueous solutions each contain a nickel salt, a reducing agent and an alkali, and each aqueous solution does not contain the other two components other than the respective components. The alkali used is the same as in the above case (i).
[0056] In either case of (i) or (ii) above, the concentration of the nickel salt in the aqueous solution is preferably from 10 to 1,000 g / L, more preferably from 50 to 500 g / L. The concentration of the reducing agent is preferably 100 to 1,000 g / L, more preferably 100 to 800 g / L, when a phosphorus compound is used as the reducing agent, preferably 5 to 200 g / L, more preferably 10 to 100 g / L, when a boron compound is used as the reducing agent, and preferably 5 to 200 g / L, more preferably 10 to 100 g / L, when hydrazine or its derivatives are used as the reducing agent, preferably 5 to 200 g / L, more preferably 10 to 100 g / L. The concentration of the alkali is preferably from 5 to 500 g / L, more preferably from 10 to 200 g / L.
[0057] The protrusion forming step may be performed continuously after the conductive layer forming step, or after the conductive layer forming step, the core particles on which the conductive layer is formed may be separated from the electroless nickel plating solution, and then the protrusion forming step may be performed. When the core particles on which the conductive layer is formed are separated from the electroless nickel plating solution, the core particles on which the conductive layer is formed may be separated from the plating solution by a method such as filtration after the conductive layer forming step. After the separation, the core particles on which the conductive layer is formed are newly dispersed in water to prepare an aqueous slurry, and an aqueous solution in which a complexing agent is dissolved in a concentration range of preferably 1 to 100 g / L, more preferably 5 to 50 g / L, is added thereto, and a dispersant is dissolved in a concentration range of preferably 0.5 to 30 g / L, more preferably 1 to 10 g / L, to prepare an aqueous slurry. The aqueous solution described in (i) or (ii) may be added to the prepared aqueous slurry to perform the protrusion forming step. In this manner, a conductive layer having protrusions can be formed.
[0058] The conductive particles having protrusions formed thereon in the protrusion forming step are subjected to a step of leveling the height of the protrusions (hereinafter also referred to as a "leveling step") to level the height of the protrusions. The leveling step limits the variation in the height of the protrusions to the above range, thereby obtaining the present conductive particles. In the leveling process, the height of the protrusions formed in the protrusion forming process is lowered by polishing the top portions of the protrusions obtained in the protrusion forming process, thereby making it possible to keep the variation in the height of the protrusions within a predetermined range.
[0059] Methods for polishing the top portions of the protrusions include, for example, a method of mixing a mixed media used in a ball mill, a bead mill, etc. with the conductive particles obtained in the protrusion formation process, a method of mixing an abrasive with the conductive particles obtained in the protrusion formation process, a method of mixing the conductive particles obtained in the protrusion formation process with each other, and a method of rotating the conductive particles obtained in the protrusion formation process on a flat surface such as a belt.
[0060] When mixing the mixed media with the conductive particles, the material of the mixed media is preferably a material having a hardness equal to or greater than that of the material of the protrusions of the conductive particles. Examples of the mixing method include a method using a stirrer with stirring blades, a method of mixing in a container that rotates or revolves or both, and a method of mixing in a vibrating container. Examples of materials for the mixed media include zirconia, zircon, agate, alumina, iron, stainless steel, and glass.
[0061] When mixing the abrasive with the conductive particles obtained in the protrusion forming step, examples of the abrasive include diamond, boron nitride, silicon carbide, aluminum oxide, etc. The method of mixing with the abrasive includes the same method as the method of mixing the mixed media with the conductive particles. As a method for mixing the conductive particles, the same methods as those for mixing the mixing medium and the conductive particles can be used.
[0062] When the conductive particles obtained in the protrusion forming process are rotated on a flat surface such as a belt, the material of the flat surface is preferably a material having a hardness equal to or greater than that of the material of the protrusions of the conductive particles. The conductive particles obtained in the protrusion forming process may be rotated so as to fall on an inclined flat surface, and moved on the flat surface. The conductive particles obtained in the protrusion forming process may also be moved in the opposite direction on a flat surface moving in a fixed direction.
[0063] In each of the polishing methods, the relationship between the polishing conditions and the height of the protrusions may be measured in advance, and the polishing conditions may be determined in advance so that the variation in the height of the protrusions is within the range of the conductive particles. Also, the variation in the height of the protrusions may be measured over time while polishing, and the polishing may be terminated when the variation in the height of the protrusions falls within the range of the conductive particles based on the results. In the same manner, the height of the protrusions can be set to the preferred range.
[0064] In the process of lowering the height of the protrusions in the leveling step, the tops of the protrusions can be polished to have a flat surface, thereby making the tops of the protrusions approximately flat. In addition, by lowering the height of the protrusions in accordance with the curvature of the surface of the core material particles, the radius of curvature of the tops of the protrusions, Ra, and the radius of curvature of the outer surface of the conductive layer, Rb, can be made to have the preferred relationship.
[0065] The present production method may further include a step of heat-treating the material after the leveling step under a vacuum of 1,000 Pa or less, preferably 0.01 Pa to 900 Pa, and particularly preferably 0.1 Pa to 500 Pa, at a temperature of 200° C. to 600° C., preferably 250° C. to 500° C., and particularly preferably 300° C. to 450° C. By heating the conductive particles while maintaining such a vacuum state, the metal in the conductive layer is less likely to undergo side reactions even at high temperatures, and crystallization progresses, resulting in low electrical resistance and excellent electrical conductivity. Note that the degree of vacuum in this invention is an absolute pressure, i.e., a value when an absolute vacuum is set to 0.
[0066] The heat treatment time in the heat treatment step is preferably 0.1 to 10 hours, more preferably 0.5 to 5 hours. By adopting this treatment time, it is possible to suppress an increase in manufacturing costs, and also to suppress the denaturation of the core particles and the conductive layer due to the thermal history, thereby minimizing the impact on quality. The heat treatment time is the time from when the target treatment temperature is reached to when the heat treatment is completed.
[0067] The heat treatment step may be performed while the conductive particles are left stationary or while stirring. When the heat treatment is performed while the conductive particles are left stationary, it is preferable to leave the conductive particles stationary at a thickness of 0.1 mm to 100 mm. By leaving the conductive particles stationary at this thickness, the heat treatment of the conductive layer can be successfully performed and the manufacturing cost can be reduced.
[0068] The heat treatment step is carried out after the container containing the conductive particles is depressurized to a vacuum, in a stationary state or with stirring. At this time, the gas phase of the container containing the conductive particles may be replaced with an inert gas such as nitrogen before depressurizing to a vacuum, or the container may be depressurized to a vacuum as is. The heat treatment may be carried out multiple times as necessary.
[0069] The heat treatment step is preferably carried out by reaching a vacuum of 1,000 Pa or less, preferably 0.01 to 900 Pa, particularly preferably 0.1 to 500 Pa, at room temperature, maintaining the pressure for 5 to 60 minutes, more preferably 10 to 50 minutes, and then raising the temperature to the treatment temperature. This operation can prevent oxidation of the conductive layer due to oxygen or moisture in the heating atmosphere or the conductive particles, and can reduce the connection resistance.
[0070] After the heat treatment step, it is preferable to lower the temperature to 50°C or less, or even 40°C or less while maintaining the degree of vacuum, and then release the vacuum. The reason for this is that if the vacuum is released at the temperature immediately after the heat treatment, the oxidation of the conductive layer may be promoted if oxygen or moisture is present in the atmosphere, which may increase the connection resistance. In addition, the vacuum may be released in normal air from the viewpoint of production costs, but from the viewpoint of preventing the oxidation of the conductive layer, it is more preferable to release the vacuum by purging with an inert gas such as nitrogen, argon, or helium, or a non-oxidizing gas such as a hydrogen-nitrogen mixed gas.
[0071] The conductive particles can be suitably used as a conductive material such as a conductive filler for a conductive adhesive as described later. The conductive material containing the conductive particles and an insulating resin (hereinafter also referred to as the "conductive material") is preferably further coated with an insulating resin on its surface to prevent short circuits between the conductive particles. The insulating resin coating is formed so that the surface of the conductive particles is not exposed as much as possible when no pressure is applied, and is destroyed by heat and pressure applied when two electrodes are bonded using the conductive adhesive, exposing at least the protruding parts of the surface of the conductive particles. The thickness of the insulating resin can be about 0.1 to 0.5 μm. The insulating resin may cover the entire surface of the conductive particles, or may only cover a part of the surface of the conductive particles.
[0072] Examples of insulating resins include resins made of organic polymers such as phenol resin, urea resin, melamine resin, allyl resin, furan resin, polyester resin, epoxy resin, silicone resin, polyamide-imide resin, polyimide resin, polyurethane resin, fluororesin, polyolefin resins such as polyethylene, polypropylene, and polybutylene, polyalkyl(meth)acrylate resin, poly(meth)acrylic acid resin, polystyrene resin, acrylonitrile-styrene-butadiene resin, vinyl resin, polyamide resin, polycarbonate resin, polyacetal resin, ionomer resin, polyethersulfone resin, polyphenyloxide resin, polysulfone resin, polyvinylidene fluoride resin, ethyl cellulose resin, and cellulose acetate resin.
[0073] Methods for coating the surfaces of conductive particles with an insulating resin to form an insulating coating layer include chemical methods such as coacervation, interfacial polymerization, in situ polymerization, and liquid curing coating; physico-mechanical methods such as spray drying, air suspension coating, vacuum deposition coating, dry blending, hybridization, electrostatic coalescence, melting dispersion cooling, and inorganic encapsulation; and physico-chemical methods such as interfacial precipitation.
[0074] The organic polymer constituting the insulating resin may contain a monomer component containing an ionic group in the polymer structure, provided that the organic polymer is non-conductive, from the viewpoint of improving adhesion with the conductive particles. The monomer component containing an ionic group may be either a crosslinkable monomer component or a non-crosslinkable monomer component. It is preferable that the organic polymer is formed using a monomer component in which at least one of the crosslinkable monomer component and the non-crosslinkable monomer component has an ionic group. The "monomer component" refers to a structure derived from a monomer in the organic polymer, and is a component derived from a monomer. By subjecting a monomer containing an ionic group to polymerization, an organic polymer containing a monomer component containing an ionic group as a constituent unit is formed.
[0075] The ionic group is preferably present in the organic polymer constituting the insulating resin. The ionic group is preferably chemically bonded to the monomer component constituting the organic polymer. Whether or not the ionic group is present at the interface of the organic polymer can be determined by observing whether or not the insulating resin is attached to the surface of the conductive particle by scanning electron microscope observation when the insulating resin containing the organic polymer having the ionic group is formed on the surface of the conductive particle.
[0076] Examples of the ionic group include onium-based functional groups such as a phosphonium group, an ammonium group, a sulfonium group, etc. Among these, from the viewpoint of increasing the adhesion between the conductive particle and the insulating resin and forming a conductive particle having both insulating properties and conduction reliability at a high level, an ammonium group or a phosphonium group is preferable, and a phosphonium group is more preferable.
[0077] The onium functional group is preferably one represented by the following general formula (1).
[0078] [ka] In the general formula (1), X is a phosphorus atom, a nitrogen atom, or a sulfur atom, and R may be the same or different and is a hydrogen atom, a linear, branched, or cyclic alkyl group, or an aryl group. n is 1 when X is a nitrogen atom or a phosphorus atom, and is 0 when X is a sulfur atom. * is a bond.
[0079] Counterions for the ionic groups include, for example, halide ions. Examples of halide ions include Cl - , F - , Br - , I - Examples include:
[0080] In the general formula (1), examples of the linear alkyl group represented by R include linear alkyl groups having 1 to 20 carbon atoms, and specific examples thereof include a methyl group, an ethyl group, a n-propyl group, a n-butyl group, a n-pentyl group, a n-hexyl group, a n-heptyl group, a n-octyl group, a n-nonyl group, a n-decyl group, a n-undecyl group, a n-dodecyl group, a n-tridecyl group, a n-tetradecyl group, a n-pentadecyl group, a n-hexadecyl group, a n-heptadecyl group, a n-octadecyl group, a n-nonadecyl group, and a n-icosyl group.
[0081] In the general formula (1), examples of the branched alkyl group represented by R include branched alkyl groups having 3 to 8 carbon atoms, and specific examples thereof include an isopropyl group, an isobutyl group, a s-butyl group, a t-butyl group, an isopentyl group, a s-pentyl group, a t-pentyl group, an isohexyl group, a s-hexyl group, a t-hexyl group, and an ethylhexyl group.
[0082] In the general formula (1), examples of the cyclic alkyl group represented by R include cycloalkyl groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, and a cyclooctadecyl group.
[0083] In the general formula (1), examples of the aryl group represented by R include a phenyl group, a benzyl group, a tolyl group, and an o-xylyl group.
[0084] In the general formula (1), R is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, and even more preferably an alkyl group having 1 to 8 carbon atoms. It is also more preferable that R in the general formula (1) is a linear alkyl group. Such a configuration of the onium functional group increases the adhesion between the insulating resin and the conductive particles to ensure insulation, and further improves the reliability of conduction during thermocompression bonding.
[0085] From the viewpoints of facilitating the acquisition of monomers and the synthesis of polymers, as well as increasing the efficiency of production of insulating resins, it is preferable that the organic polymer having an ionic group that constitutes the insulating resin has a constitutional unit represented by the following general formula (2) or general formula (3).
[0086] [ka] In the general formula (2), X, R, and n are the same as those in the general formula (1). m is an integer of 0 to 5. - indicates a monovalent anion. When m is 0, it indicates that X is directly bonded to the benzene ring.
[0087] [ka] In the general formula (3), X, R and n are the same as those in the general formula (1). - indicates a monovalent anion. m 1 is an integer of 1 to 5. R5 is a hydrogen atom or a methyl group.
[0088] As examples of R in the general formula (2) and the general formula (3), the explanation of the functional group of R in the general formula (1) above is appropriately applied. The ionic group may be bonded to the para-position, ortho-position, or meta-position relative to the CH group of the benzene ring in the general formula (2), and is preferably bonded to the para-position. In the general formulas (2) and (3), monovalent An - Suitable examples of the halide ion include Cl. - , F - , Br - , I - Examples include:
[0089] In the general formula (2), m is preferably an integer of 0 to 2, more preferably 0 or 1, and particularly preferably 1. In the general formula (3), m 1 is preferably 1 or more and 3 or less, more preferably 1 or 2, and most preferably 2.
[0090] The organic polymer having an ionic group is preferably composed of a monomer component having, for example, an onium-based functional group and an ethylenically unsaturated bond. From the viewpoint of facilitating the availability of monomers and the synthesis of polymers and increasing the production efficiency of insulating resins, the organic polymer having an ionic group also preferably contains a non-crosslinkable monomer component.
[0091] Examples of non-crosslinkable monomers having an onium functional group and an ethylenically unsaturated bond include ammonium group-containing monomers such as N,N-dimethylaminoethyl methacrylate, N,N-dimethylaminopropylacrylamide, and N,N,N-trimethyl-N-2-methacryloyloxyethyl ammonium chloride; monomers having a sulfonium group such as phenyl dimethylsulfonium methyl sulfate methacrylate; 4-(vinylbenzyl)triethylphosphonium chloride, 4-(vinylbenzyl)trimethylphosphonium chloride, and 4-(vinylbenzyl)tributyl Examples of monomers having a phosphonium group include phosphonium chloride, 4-(vinylbenzyl)trioctylphosphonium chloride, 4-(vinylbenzyl)triphenylphosphonium chloride, 2-(methacryloyloxyethyl)trimethylphosphonium chloride, 2-(methacryloyloxyethyl)triethylphosphonium chloride, 2-(methacryloyloxyethyl)tributylphosphonium chloride, 2-(methacryloyloxyethyl)trioctylphosphonium chloride, and 2-(methacryloyloxyethyl)triphenylphosphonium chloride. The organic polymer having an ionic group may contain two or more non-crosslinkable monomer components.
[0092] The organic polymer constituting the insulating resin may have an ionic group bonded to all of the monomer components, or may have an ionic group bonded to a portion of all of the organic polymer's structural units. When an ionic group is bonded to a portion of all of the organic polymer's structural units, the proportion of the monomer components to which the ionic group is bonded is preferably 0.01 mol% or more and 99 mol% or less, more preferably 0.02 mol% or more and 95 mol% or less. Here, when the organic polymer has an ethylenically unsaturated bond, the number of monomer components in the organic polymer is counted as one monomer structural unit, with a structure derived from one ethylenically unsaturated bond being counted as one monomer structural unit. When an ionic group is contained in both a crosslinkable monomer and a non-crosslinkable monomer, the proportion of the monomer components is the total amount.
[0093] The insulating resin may be coated in a form in which a plurality of insulating fine particles made of insulating resin are arranged in layers, or in which the insulating resin forms a continuous film.
[0094] When the insulating resin is made of insulating fine particles, the conductive particles coated with the insulating fine particles are thermocompressed between the electrodes, whereby the insulating fine particles melt, deform, peel off, or move on the conductive particle surface, exposing the metal surface of the conductive particle in the thermocompression-bonded portion, thereby enabling conduction between the electrodes and obtaining connectivity. Meanwhile, the surface portion of the conductive particle facing in a direction other than the thermocompression direction is generally maintained in a state where the conductive particle surface is coated with the insulating fine particles, so that conduction in a direction other than the thermocompression direction is prevented.
[0095] Since the insulating fine particles contain the ionic groups on their surfaces, they are easily attached to the conductive particles, and this allows the proportion of the conductive particle surface covered with the insulating fine particles to be sufficient, and effectively prevents the insulating fine particles from peeling off from the conductive particles, etc. Therefore, the insulating fine particles are more likely to exhibit a short-circuit prevention effect in a direction different from that between the opposing electrodes, and improvement in insulation in that direction can be expected.
[0096] The shape of the insulating fine particles is not particularly limited, and may be spherical or may be a shape other than spherical. Examples of shapes other than spherical include fibrous, hollow, plate-like, and needle-like. The insulating fine particles may also have a large number of protrusions on their surface or may be amorphous. Spherical insulating fine particles are preferred in terms of adhesion to conductive particles and ease of synthesis.
[0097] The average particle diameter of the insulating fine particles is preferably 10 nm or more and 3,000 nm or less, more preferably 15 nm or more and 2,000 nm or less. When the average particle diameter of the insulating fine particles is within the above range, the obtained coated particles do not cause a short circuit in a direction different from that between the opposing electrodes, and it is easy to ensure conduction between the opposing electrodes. The average particle diameter of the insulating fine particles is a value measured by observation using a scanning electron microscope, and specifically, is measured by the method described in the examples below.
[0098] The particle size distribution of insulating fine particles measured by the above-mentioned method usually has a certain width. In general, the width of the particle size distribution of a powder is represented by the coefficient of variation (hereinafter also referred to as "CV") shown in the following formula (4). CV(%)=(standard deviation / average particle diameter)×100...(4) If the CV is large, the particle size distribution is wide, whereas if the CV is small, the particle size distribution is sharp. The CV of the insulating fine particles used in the present conductive material is preferably 0.1% to 20%, more preferably 0.5% to 15%, and particularly preferably 1% to 10%. By having the CV in this range, there is an advantage that the thickness of the coating layer made of the insulating fine particles can be made uniform.
[0099] Alternatively, instead of the insulating fine particles arranged in layers, the insulating resin may be a continuous film. When the continuous film is an insulating resin having an ionic group, the conductive particles are thermocompressed between electrodes, whereby the continuous film melts, deforms, or peels off, exposing the surface of the conductive particles, thereby enabling electrical conduction between the electrodes and providing connectivity. In particular, the conductive particles are thermocompressed between the electrodes, whereby the continuous film breaks, resulting in many conductive particles with exposed surfaces. On the other hand, in the surface portion of the conductive particle facing in a direction different from the thermocompression bonding direction, the state in which the conductive particle is covered with the continuous film is generally maintained, so that conduction in a direction other than the thermocompression bonding direction is prevented. When the insulating resin is a continuous film, it is preferable that the continuous film has ionic groups on the surface.
[0100] The thickness of the continuous film is preferably 10 nm or more from the viewpoint of improving insulation in a direction different from the direction between the opposing electrodes, and is preferably 3,000 nm or less from the viewpoint of facilitating electrical conduction between the opposing electrodes. From this viewpoint, the thickness of the continuous film is preferably 10 nm or more and 3,000 nm or less, and more preferably 15 nm or more and 2,000 nm or less.
[0101] As with the insulating fine particles, the ionic group in the continuous film is preferably part of the chemical structure of the insulating resin as part of the insulating resin constituting the continuous film. The ionic group in the continuous film is preferably contained in at least one structure of the structural unit of the insulating resin constituting the continuous film. The ionic group is preferably chemically bonded to the insulating resin constituting the continuous film, more preferably bonded to the side chain of the insulating resin.
[0102] When the conductive material has a continuous film of insulating resin, it is preferable that the conductive particles are coated with insulating fine particles having ionic groups on their surfaces, and then the insulating fine particles are heated to obtain a continuous film, or the insulating fine particles are dissolved in an organic solvent to obtain a continuous film. As described above, the insulating fine particles having ionic groups are easily attached to the conductive particles, which makes the proportion of the insulating fine particles on the conductive particle surface covered with the insulating fine particles sufficient, and makes it easier to prevent the insulating fine particles from peeling off from the conductive particles. Therefore, the continuous film obtained by heating or dissolving the insulating fine particles that cover the conductive particles can have a uniform thickness and a high proportion of the conductive particle surface covered with the insulating fine particles.
[0103] The conductive particles may be treated with a surface treatment agent from the viewpoint of increasing the affinity with the insulating resin and improving adhesion. Examples of the surface treatment agent include benzotriazole compounds, titanium compounds, higher fatty acids or derivatives thereof, phosphates, phosphites, etc. These may be used alone or in combination as necessary.
[0104] The surface treatment agent may or may not be chemically bonded to the surface of the conductive particle. The surface treatment agent only needs to be present on the surface of the conductive particle, and in this case, the surface treatment agent may be present on the entire surface of the conductive particle, or may be present only on a part of the surface.
[0105] The triazole-based compounds include compounds having a nitrogen-containing heterocyclic structure having three nitrogen atoms in a five-membered ring.
[0106] Examples of the triazole-based compound include compounds having a triazole monocyclic structure that is not condensed with other rings, and compounds having a ring structure in which a triazole ring is condensed with other rings. Examples of the other rings include a benzene ring and a naphthalene ring.
[0107] Among these, compounds having a ring structure in which a triazole ring is condensed with another ring are preferred because of their excellent adhesion to insulating resins, and benzotriazole-based compounds, which are compounds having a structure in which a triazole ring is condensed with a benzene ring, are particularly preferred. Benzotriazole compounds include those represented by the following general formula (4).
[0108] [ka] In the general formula (4), R 11 is a negative charge, a hydrogen atom, an alkali metal, an optionally substituted alkyl group, an amino group, a formyl group, a hydroxyl group, an alkoxy group, a sulfonic acid group, or a silyl group, and R 12 , R 13 , R 14 and R 15 each independently represents a hydrogen atom, a halogen atom, an optionally substituted alkyl group, a carboxyl group, a hydroxyl group, or a nitro group.
[0109] R in the general paper formula (4) 11 Examples of the alkali metal represented by R include lithium, sodium, and potassium. 11 The alkali metal represented by R in general formula (4) is an alkali metal cation. 11 When is an alkali metal, R 11 The bond between the nitrogen atom and the alkyl group may be an ionic bond. R in general formula (4) 11 , R 12 , R 13 , R 14 and R 15 Examples of the alkyl group represented by the formula (I) include those having 1 to 20 carbon atoms, and particularly preferably those having 1 to 12 carbon atoms. The alkyl group may be substituted, and examples of the substituent include an amino group, an alkoxy group, a carboxyl group, a hydroxyl group, an aldehyde group, a nitro group, a sulfonic acid group, a quaternary ammonium group, a sulfonium group, a sulfonyl group, a phosphonium group, a cyano group, a fluoroalkyl group, a mercapto group, and a halogen atom. R 11 Preferred alkoxy groups represented by the formula (I) include those having 1 to 12 carbon atoms. do. Also, R 12 , R 13 , R 14 and R 15 The number of carbon atoms of the alkoxy group as a substituent of the alkyl group represented by the general formula (4) is preferably 1 to 12. 12 , R 13 , R 14 and R 15 Examples of the halogen atom represented by the formula (I) include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0110] Specific examples of triazole compounds include compounds having a single triazole ring structure such as 1,2,3-triazole, 1,2,4-triazole, 3-amino-1H-1,2,4-triazole, 5-mercapto-1H-1,2,3-triazole sodium, 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole, and 3-amino-5-mercapto-1,2,4-triazole. In addition, compounds having a ring structure in which a triazole ring is condensed with another ring include benzotriazole, 1-methyl-1H-benzotriazole, 4-methyl-1H-benzotriazole, 5-methyl-1H-benzotriazole, 4-carboxy-1H-benzotriazole, 5-carboxy-1H-benzotriazole, 5-ethyl-1H-benzotriazole, and 5-propyl-1H-benzotriazole. 1H-benzotriazole-1-carboxyaldehyde, 1-(chloromethyl)-1H-benzotriazole, 1-hydroxy-6-(trifluoromethyl)benzotriazole, benzotriazole butyl ester, 4-carboxyl-1H-benzotriazole butyl ester, 4-carboxyl-1H-benzotriazole octyl ester, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol, tetrabutylphosphonium benzotriazolate, 1H-benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate, 1-(formamidomethyl)-1H-benzotriazole, 1-[bis(dimethylamino)methylene]-1H-benzotriazolium 3- Oxide hexafluorophosphate, 1-[bis(dimethylamino)methylene]-1H-benzotriazolium 3-oxide tetrafluoroborate, (6-chloro-1H-benzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate, O-(benzotriazol-1-yl)-N,N,N',N'-bis(tetramethylene)uronium hexafluorophosphate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium Tetrafluoroborate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-(benzotriazol-1-yl)-N,N,N',N'-bis(pentamethylene)uronium hexafluorophosphate, 1-(trimethylsilyl)-1H-benzotriazole, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]benzotriazole, 1-(trifluoromethanesulfonyl)-1H-benzotriazole, (trimethylsilyl)-1H-benzotriazole, trifluoroacetyl)benzotriazole, tris(1H-benzotriazol-1-yl)methane, 9-(1H-benzotriazol-1-ylmethyl)-9H-carbazole, [(1H-benzotriazol-1-yl)methyl]triphenylphosphonium chloride, 1-(isocyanomethyl)-1H-benzotriazole, 1-[(9H-fluoren-9-ylmethoxy)carbonyloxy]benzotriazole, 1,2,3-benzotriazole sodium salt, naphthotriazole, and the like.
[0111] As the titanium-based compound, for example, a compound having a structure represented by the following general formula (5) is particularly preferred because, when present on the surface of a conductive particle, affinity between the insulating resin and the conductive particle can be easily obtained and the compound is easily dispersed in a solvent, allowing the conductive particle surface to be uniformly treated.
[0112] [ka] In the general formula (5), R 21 is a divalent or trivalent group, R 22 is an aliphatic hydrocarbon group having 2 to 30 carbon atoms, an aryl group having 6 to 22 carbon atoms, or an arylalkyl group having 7 to 23 carbon atoms, p and r are each an integer of 1 to 3, p+r=4 is satisfied, q is an integer that is 1 or 2, R 21 is a divalent group, q is 1, and R 21 When R is a trivalent group, q is 2. When q is 2, multiple R 22 may be the same or different. * represents a bond.
[0113] R 22 Examples of the aliphatic hydrocarbon group having 4 to 28 carbon atoms, represented by the formula (1), include methyl group, ethyl group, propyl group, butyl group, pentyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, icosyl group, henicosyl group, docosyl group, etc. Examples of the unsaturated aliphatic hydrocarbon group include alkenyl groups such as dodecenyl group, tridecenyl group, tetradecenyl group, pentadecenyl group, hexadecenyl group, heptadecenyl group, nonadecenyl group, icosenyl group, eicosenyl group, henicosyl group, and docosenyl group. Examples of the aryl group having 6 to 22 carbon atoms include a phenyl group, a tolyl group, a naphthyl group, and an anthryl group. Examples of the arylalkyl group having 7 to 23 carbon atoms include a benzyl group, a phenethyl group, and a naphthylmethyl group. As the hydrophobic group, a straight-chain or branched-chain aliphatic hydrocarbon group is particularly preferred, and a straight-chain aliphatic hydrocarbon group is particularly preferred. In order to increase the affinity between the insulating resin and the conductive particles, the aliphatic hydrocarbon group as the hydrophobic group is more preferably one having 4 to 28 carbon atoms, and most preferably one having 6 to 24 carbon atoms.
[0114] R 21 Examples of the divalent group represented by the formula include -O-, -COO-, -OCO-, and -OSO2-. 21 Examples of the trivalent group represented by the formula include -P(OH)(O-)2, -OPO(OH)-OPO(O-)2, and the like.
[0115] In the general formula (5), * is a bond, which may be bonded to the metal coating of the conductive particle, or may be bonded to another group, etc. In this case, examples of the other group include a hydrocarbon group, specifically an alkyl group having 1 to 12 carbon atoms.
[0116] The titanium-based compound having the structure represented by the general formula (5) is, for example, 21 Compounds having a structure in which R is a divalent group are preferred in terms of availability and the ability to be processed without impairing the conductive properties of the conductive particles. 21 The structure in which is a divalent group is represented by the following general formula (6).
[0117] [ka] In the general formula (6), R 21 is a group selected from -O-, -COO-, -OCO-, and -OSO2-; p, r, and R 22 has the same meaning as general formula (II).
[0118] In the general formulas (5) and (6), r is preferably 2 or 3 from the viewpoint of improving the adhesion between the insulating resin and the conductive layer, and r is most preferably 3.
[0119] Specific examples of titanate compounds used in the surface treatment include isopropyl triisostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraisopropyl(dioctyl phosphite) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, and bis(dioctyl pyrophosphate)ethylene titanate. These may be used alone or in combination of two or more. These titanate compounds are commercially available, for example, from Ajinomoto Fine-Techno Co., Ltd.
[0120] The higher fatty acid is preferably a saturated or unsaturated linear or branched mono- or polycarboxylic acid, more preferably a saturated or unsaturated linear or branched monocarboxylic acid, and even more preferably a saturated or unsaturated linear monocarboxylic acid. The fatty acid preferably has 7 or more carbon atoms. The derivative refers to a salt or amide of the fatty acid.
[0121] The higher fatty acid or its derivative used in the surface treatment preferably has 7 to 23 carbon atoms, more preferably 10 to 20 carbon atoms. Examples of such higher fatty acids or their derivatives include saturated fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, and stearic acid, unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, and arachidonic acid, and metal salts or amides thereof. Examples of metal salts of higher fatty acids include salts of alkali metals, alkaline earth metals, transition metals such as Zr, Cr, Mn, Fe, Co, Ni, Cu, and Ag, and metals other than transition metals such as Al and Zn, and are preferably polyvalent metal salts such as Al, Zn, W, and V. The higher fatty acid metal salts may be mono-, di-, tri-, and tetra-forms depending on the valence of the metal. The higher fatty acid metal salts may be any combination of these.
[0122] As the phosphate ester and the phosphite ester, those having an alkyl group having 6 to 22 carbon atoms are preferably used. Examples of phosphate esters include hexyl phosphate, heptyl phosphate, monooctyl phosphate, monononyl phosphate, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl phosphate, monotetradecyl phosphate, and monopentadecyl phosphate. Examples of phosphite esters include hexyl phosphite, heptyl phosphite, monooctyl phosphite, monononyl phosphite, monodecyl phosphite, monoundecyl phosphite, monododecyl phosphite, monotridecyl phosphite, monotetradecyl phosphite, and monopentadecyl phosphite.
[0123] The surface treatment agent used in the surface treatment has excellent affinity with the insulating resin and is preferably a triazole-based compound or a titanium-based compound from the viewpoint of the effect of increasing the coverage rate of the insulating resin, and particularly preferably benzotriazole, 4-carboxybenzotriazole, isopropyl triisostearoyl titanate, or tetraisopropyl (dioctyl phosphite) titanate.
[0124] The method of treating the conductive particles with a surface treatment agent includes dispersing the conductive particles in a solution of the surface treatment agent and then filtering the dispersed particles. Before the treatment with the surface treatment agent, the conductive particles may be treated with another treatment agent or may be untreated. The concentration of the surface treatment agent in the solution of the surface treatment agent in which the conductive particles are dispersed is, for example, 0.01% by mass or more and 10.0% by mass or less. Examples of the solvent for the solution of the surface treatment agent include water, alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, isopentyl alcohol, and cyclohexanol, ketones such as acetone, methyl isobutyl ketone, methyl ethyl ketone, and methyl-n-butyl ketone, esters such as methyl acetate and ethyl acetate, ethers such as diethyl ether and ethylene glycol monoethyl ether, normal hexane, cyclohexanone, toluene, 1,4-dioxane, N,N-dimethylformamide, and tetrahydrofuran. It is preferable to disperse the conductive particles after the surface treatment, which have been dispersed and filtered, again in a solvent to remove excess surface treatment agent.
[0125] The surface treatment of the conductive particles with the surface treatment agent can be carried out by mixing the conductive particles, the surface treatment agent, and a solvent at room temperature. Alternatively, the conductive particles and the surface treatment agent may be mixed in a solvent and then heated to promote the reaction. The heating temperature is, for example, 30°C or higher and 50°C or lower.
[0126] The conductive particles have low connection resistance and excellent connection reliability, and are therefore suitable for use as a conductive material for connecting electrodes of an anisotropic conductive film (ACF), a heat seal connector (HSC), or a liquid crystal display panel to a circuit board of a driving LSI chip. The conductive particles may be used as they are as a conductive material, or the conductive particles may be dispersed in a binder resin to form a conductive material. The conductive material may be used as it is as a conductive material, or the conductive material may be dispersed in a binder resin. The other forms of the conductive material are not particularly limited, and in addition to the above, examples include anisotropic conductive paste, conductive adhesive, anisotropic conductive ink, and the like.
[0127] The binder resin may be a thermoplastic resin or a thermosetting resin, etc. Examples of the thermoplastic resin include an acrylic resin, a styrene resin, an ethylene-vinyl acetate resin, a styrene-butadiene block copolymer, etc., and examples of the thermosetting resin include an epoxy resin, a phenol resin, a urea resin, a polyester resin, a urethane resin, a polyimide resin, etc.
[0128] In addition to the conductive particles and binder resin of the present invention, the conductive material may contain, as necessary, a tackifier, a reactive auxiliary, an epoxy resin curing agent, a metal oxide, a photoinitiator, a sensitizer, a curing agent, a vulcanizing agent, an anti-degradation agent, a heat resistance additive, a thermal conductivity improver, a softener, a colorant, various coupling agents, or a metal deactivator.
[0129] In the conductive material, the amount of the conductive particles used may be appropriately determined depending on the application. From the viewpoint of easily achieving electrical conduction without the conductive particles coming into contact with each other, the amount is preferably, for example, 0.01 parts by mass or more and 50 parts by mass or less, and more preferably 0.03 parts by mass or more and 40 parts by mass or less, per 100 parts by mass of the conductive material.
[0130] The conductive particles of the present invention are particularly suitable for use as a conductive filler for a conductive adhesive, among the above-mentioned forms of conductive materials.
[0131] The conductive adhesive is preferably used as an anisotropic conductive adhesive that is disposed between two substrates on which a conductive base material is formed, and that adheres the conductive base material to provide electrical conductivity by heating and pressurization. This anisotropic conductive adhesive contains the conductive particles of the present invention and an adhesive resin. Any adhesive resin that is insulating and is used as an adhesive resin can be used without particular limitations. It may be either a thermoplastic resin or a thermosetting resin, and it is preferable that the adhesive performance is expressed by heating. Such adhesive resins include, for example, a thermoplastic type, a thermosetting type, an ultraviolet curing type, and the like. In addition, there are so-called semi-thermosetting types that show intermediate properties between the thermoplastic type and the thermosetting type, and composite types of a thermosetting type and an ultraviolet curing type. These adhesive resins can be appropriately selected according to the surface characteristics of the circuit board or the like to be adhered and the form of use. In particular, an adhesive resin that includes a thermosetting resin is preferable because it has excellent material strength after adhesion.
[0132] Specific examples of adhesive resins include those prepared using as the main component one or a combination of two or more selected from ethylene-vinyl acetate copolymer, carboxyl-modified ethylene-vinyl acetate copolymer, ethylene-isobutyl acrylate copolymer, polyamide, polyimide, polyester, polyvinyl ether, polyvinyl butyral, polyurethane, SBS block copolymer, carboxyl-modified SBS copolymer, SIS copolymer, SEBS copolymer, maleic acid-modified SEBS copolymer, polybutadiene rubber, chloroprene rubber, carboxyl-modified chloroprene rubber, styrene-butadiene rubber, isobutylene-isoprene copolymer, acrylonitrile-butadiene rubber (hereinafter referred to as NBR), carboxyl-modified NBR, amine-modified NBR, epoxy resin, epoxy ester resin, acrylic resin, phenolic resin, silicone resin, etc. Among these, styrene-butadiene rubber and SEBS are preferable as thermoplastic resins because they have excellent reworkability. As thermosetting resins, epoxy resins are preferable. Of these, epoxy resins are most preferred because of their advantages of high adhesive strength, excellent heat resistance and electrical insulation, low melt viscosity, and ability to connect at low pressure.
[0133] As the epoxy resin, any commonly used epoxy resin can be used as long as it is a polyhydric epoxy resin having two or more epoxy groups in one molecule. Specific examples include novolac resins such as phenol novolac and cresol novolac, polyhydric phenols such as bisphenol A, bisphenol F, bisphenol AD, resorcin, and bishydroxydiphenyl ether, polyhydric alcohols such as ethylene glycol, neopentyl glycol, glycerin, trimethylolpropane, and polypropylene glycol, polyamino compounds such as ethylenediamine, triethylenetetramine, and aniline, and polyvalent carboxy compounds such as adipic acid, phthalic acid, and isophthalic acid, and glycidyl-type epoxy resins obtained by reacting epichlorohydrin or 2-methylepichlorohydrin. In addition, aliphatic and alicyclic epoxy resins such as dicyclopentadiene epoxide and butadiene dimer diepoxide can be mentioned. These can be used alone or in combination of two or more.
[0134] As for the various adhesive resins, Na + Or Cl - From the viewpoint of preventing ion migration, it is preferable to use a high-purity product in which impurity ions such as those mentioned above and hydrolyzable chlorine are reduced.
[0135] The amount of conductive particles used in the anisotropic conductive adhesive is usually 0.1 to 30 parts by mass, preferably 0.5 to 25 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the adhesive resin component. By keeping the amount of conductive particles within this range, increases in connection resistance and melt viscosity are suppressed, connection reliability is improved, and connection anisotropy can be sufficiently ensured.
[0136] In addition to the conductive particles and adhesive resin described above, the anisotropic conductive adhesive may contain additives known in the art. The amount of the additives may be within a range known in the art. Examples of other additives include tackifiers, reactive assistants, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizing agents, anti-degradation agents, heat resistance additives, thermal conductivity improvers, softeners, colorants, various coupling agents, or metal deactivators.
[0137] Examples of tackifiers include rosin, rosin derivatives, terpene resins, terpene phenol resins, petroleum resins, coumarone-indene resins, styrene resins, isoprene resins, alkylphenol resins, and xylene resins. Examples of reactive auxiliaries, i.e., crosslinking agents, include polyols, isocyanates, melamine resins, urea resins, utropines, amines, acid anhydrides, and peroxides. As epoxy resin curing agents, any agent having two or more active hydrogens per minute can be used without any particular limitations. Specific examples include polyamino compounds such as diethylenetriamine, triethylenetetramine, metaphenylenediamine, dicyandiamide, and polyamidoamine; organic acid anhydrides such as phthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride; and novolac resins such as phenol novolac and cresol novolac. These can be used alone or in combination of two or more. If necessary, a latent curing agent may be used. Examples of usable latent curing agents include imidazoles, hydrazides, boron trifluoride-amine complexes, sulfonium salts, aminimides, polyamine salts, dicyandiamide, and modified products thereof. These can be used alone or in combination of two or more.
[0138] The anisotropic conductive adhesive is manufactured using a manufacturing device commonly used in the technical field. For example, the adhesive resin is mixed with conductive particles and a curing agent or various additives as necessary, and is manufactured by mixing in an organic solvent when the adhesive resin is a thermosetting resin, or by melt-kneading at a temperature above the softening point of the adhesive resin, specifically preferably about 50 to 130°C, more preferably about 60 to 110°C, when the adhesive resin is a thermoplastic resin. The anisotropic conductive adhesive thus obtained may be applied as a coating or in the form of a film.
[0139] The connection structure according to the present invention is obtained by connecting two circuit boards together using the conductive particles according to the present invention or the conductive material according to the present invention. Examples of the form of the connection structure include a connection structure between a flexible printed circuit board and a glass substrate, a connection structure between a semiconductor chip and a flexible printed circuit board, and a connection structure between a semiconductor chip and a glass substrate. EXAMPLES
[0140] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples.
[0141] The properties in the examples were measured by the following methods. (1) Average particle size 200 particles were randomly extracted from a scanning electron microscope (SEM) photograph of the measurement subject, and the particle diameters were measured at a magnification of 10,000 times, and the arithmetic mean value was taken as the average particle diameter. (2) Thickness of the conductive layer The conductive particle was cut into two pieces, and the cross section of the cut pieces was observed and measured using a scanning electron microscope (SEM). (3) Variation in the height of protrusions The height of the protrusions was measured for the cross section of the conductive particle observed by SEM, and calculated using the following formula (1). TIFF2024030952000011.tif24151(4) Radius of curvature For the cross-section of the conductive particles observed by SEM, the radius of the circumscribing circle circumscribing the top part of the cross-section of each protrusion was measured as Ra, and the radius of the circumscribing circle circumscribing the surface of the lower layer of the conductive layer was measured as Rb. (5) Projected area of conductive particles and area of the top part of protrusions The SEM photographic images of the conductive particles were captured into an automatic image analyzer (Luzex (registered trademark) AP, manufactured by Nireco Corporation) and measured.
[0142] Example 1 (1) Pretreatment of core particles Spherical styrene-acrylate-silica composite resin particles with an average particle size of 2.0 μm were used as core particles. 9 g of the particles were added to 200 mL of conditioner aqueous solution ("Cleaner Conditioner 231" manufactured by Rohm and Haas Electronic Materials) while stirring. The concentration of the conditioner aqueous solution was 40 mL / L. The solution was then stirred for 30 minutes at a liquid temperature of 60°C while applying ultrasonic waves to the core particles to modify their surface and disperse them. The aqueous solution was filtered, and the core particles were repulped and washed once to form a 200 mL slurry. 0.1 g of stannous chloride was added to the slurry. The mixture was stirred for 5 minutes at room temperature to perform a sensitization treatment in which tin ions are adsorbed on the surface of the core particles. The aqueous solution was then filtered, and the core particles were repulped and washed once to form a 200 mL slurry and maintained at 60°C. 1.5 mL of a 0.11 mol / L aqueous palladium chloride solution was added to the slurry. The mixture was stirred at 60°C for 5 minutes to activate the core particles, capturing palladium ions on their surfaces. The aqueous solution was then filtered, and the core particles were repulped and washed with hot water once to make a 100mL slurry. 10mL of 0.5g / L dimethylamine borane aqueous solution was added, and the mixture was stirred for 2 minutes while applying ultrasonic waves to obtain a slurry of pretreated core particles.
[0143] (2) Preparation of plating solution 3 L of electroless nickel-phosphorus plating solution was prepared from an aqueous solution of 5 g / L sodium tartrate, 2 g / L nickel sulfate hexahydrate, 10 g / L trisodium citrate, 0.1 g / L sodium hypophosphite, and 2 g / L polyethylene glycol, and heated to 70°C.
[0144] (3) Electroless plating The slurry of the pretreated core particles was added to this electroless plating bath and stirred for 5 minutes to confirm that hydrogen bubbling had stopped. 420 mL of a 224 g / L nickel sulfate aqueous solution and 420 mL of a mixed aqueous solution containing 210 g / L sodium hypophosphite and 80 g / L sodium hydroxide were continuously added to this slurry at an addition rate of 2.5 mL / min using a metering pump to start electroless plating. After the entire amount of the nickel sulfate aqueous solution and the mixed aqueous solution of sodium hypophosphite and sodium hydroxide was added, stirring was continued for 5 minutes while maintaining the temperature at 70°C. The liquid was then filtered, and the filtrate was washed three times and then dried in a vacuum dryer at 110°C to obtain conductive particles with protrusions.
[0145] (4) Processing of protruding parts 20 g of the obtained conductive particles were placed in a ball mill container together with alumina balls, ethanol was added, and the particles were crushed at 80 rpm for 6 hours. The balls and slurry were then separated and dried in a vacuum dryer at 110°C to obtain conductive particles with low protrusion height. The protrusion height of the obtained conductive particles was 100.8 nm.
[0146] (5) Vacuum heat treatment The obtained conductive particles were placed in a square container so that the thickness was 5 mm. This was placed in a vacuum heating furnace (KDF-75, manufactured by Denken Hydental Co., Ltd.) and held at a vacuum of 10 Pa for 10 minutes. The temperature was then raised and heat treatment was performed at 390°C for 2 hours. After the heat treatment, the particles were allowed to cool to room temperature (25°C), and the vacuum was released by purging with nitrogen gas to obtain heat-treated conductive particles. An SEM photograph of the obtained conductive particles is shown in Figure 2. The average particle diameter of the obtained conductive particles was 2.2 μm, the thickness of the conductive layer was 110 nm, and the height of the protrusions was 100.8 nm. The physical properties of the obtained conductive particles are shown in Table 1.
[0147] Example 2 (1) Pretreatment of core particles The same procedure as in Example 1 was carried out except that resin particles having an average particle size of 2.0 μm (Optobeads, manufactured by Nissan Chemical Industries, Ltd.) were used as the core particles, to obtain a slurry of pretreated core particles. (2) Preparation of plating solution An electroless plating solution was prepared in the same manner as in Example 1(2). (3) Electroless plating The same procedure as in Example 1(3) was carried out to obtain conductive particles having protrusions. (4) Processing of protruding parts The same procedure as in Example 1(4) was carried out to obtain conductive particles having protrusions with a height of 101 nm. (5) Vacuum heat treatment The same operation as in Example 1 was carried out to obtain heat-treated conductive particles. The average particle size of the obtained conductive particles was 2.2 μm, the thickness of the conductive layer was 94.8 nm, and the height of the protrusions was 101 nm. The physical properties of the obtained conductive particles are shown in Table 1.
[0148] Example 3 The same operations as in Example 1 were carried out up to the step (3) of electroless plating treatment in Example 1 to obtain conductive particles having protrusions. (4) Processing of protruding parts The same procedure as in Example 1 was carried out except that the obtained conductive particles were crushed for 3 hours, to obtain conductive particles having a protrusion height of 145.3 nm. (5) Vacuum heat treatment The same operation as in Example 1 was carried out to obtain heat-treated conductive particles. An SEM photograph of the obtained conductive particles is shown in FIG. 3. The average particle diameter of the obtained conductive particles was 2.2 μm, the thickness of the conductive layer was 97.8 nm, and the height of the protrusions was 145.3 nm. The physical properties of the obtained conductive particles are shown in Table 1.
[0149] Example 4 The same operations as in Example 1 were carried out up to the step (3) of electroless plating treatment in Example 1 to obtain conductive particles having protrusions. (4) Processing of protruding parts The same procedure as in Example 1 was carried out except that the obtained conductive particles were crushed using zirconia balls at 80 rpm for 4 hours, to obtain conductive particles with a protrusion height of 115.6 nm. (5) Vacuum heat treatment The same operation as in Example 1 was carried out to obtain heat-treated conductive particles. An SEM photograph of the obtained conductive particles is shown in FIG. 4. The average particle diameter of the obtained conductive particles was 2.2 μm, the thickness of the conductive layer was 95.8 nm, and the height of the protrusions was 115.6 nm. The physical properties of the obtained conductive particles are shown in Table 1.
[0150] Comparative Example 1 Conductive particles were obtained by the same procedure as in Example 1, except that (4) flat projection treatment was not performed in Example 1. The physical properties of the obtained conductive particles are shown in Table 1.
[0151] Comparative Example 2 The same operations as in Example 1 were carried out up to the step (3) of electroless plating treatment in Example 1 to obtain conductive particles having protrusions. (4) Processing of protruding parts The same procedure as in Example 1 was carried out except that the obtained conductive particles were crushed for 1 hour, to obtain conductive particles having a protrusion height of 174.9 nm. (5) Vacuum heat treatment The same operation as in Example 1 was carried out to obtain heat-treated conductive particles. An SEM photograph of the obtained conductive particles is shown in FIG. 5. The average particle diameter of the obtained conductive particles was 2.2 μm, the thickness of the conductive layer was 99.9 nm, and the height of the protrusions was 174.9 nm. The physical properties of the obtained conductive particles are shown in Table 1.
[0152] [Table 1]
[0153] [Evaluation of connection resistance and insulation] Using the conductive particles of the examples and comparative examples, the connection resistance and insulating properties were evaluated by the following methods. An insulating adhesive, which was a mixture of 100 parts by mass of epoxy resin, 150 parts by mass of hardener, and 70 parts by mass of toluene, was mixed with 15 parts by mass of the conductive particles obtained in the examples or comparative examples to obtain an insulating paste. This paste was applied to a silicone-treated polyester film using a bar coater, and then the paste was dried to form a thin film on the film. The obtained thin film-formed film was placed between a glass substrate with aluminum electrodes deposited on the entire surface and a polyimide film substrate with copper electrode patterns formed at a pitch of 50 μm, and pressed to prepare a sample for measuring the conductive resistance. Electrical connections were made to the obtained sample for measuring the conductive resistance, and the connection resistance of this sample was measured at room temperature (25°C and 50% RH) to evaluate the connection resistance. The connection resistance was evaluated using a multimeter R6552 (manufactured by Advantest Corporation) according to the following criteria. The results are shown in Table 2. ○: Resistance is less than 2Ω △: Resistance is between 2Ω and 5Ω ×: Resistance is 5Ω or more
[0154] Furthermore, the insulation was evaluated based on the rate at which short circuits occurred among the 100 samples used for measuring the electrical resistance. The insulation was evaluated by the following method. The results are shown in Table 2. ○: Short circuit occurrence rate is less than 5% △: Short circuit occurrence rate is 5% or more but less than 30% ×: Short circuit occurrence rate is 30% or more
[0155] [Table 2]
[0156] From these results, it is apparent that the conductive particles obtained in the examples have a lower connection resistance value and are superior in insulating properties compared to the conductive particles obtained in the comparative examples. [Explanation of symbols]
[0157] 1. Conductive particles 2. Core particles 3. Conductive layer 4...Protrusion 5...Plant part of protrusion 5a and 5b: Ends of flat surfaces 6. Surface of the lower layer of the conductive layer
Claims
1. Conductive particles having a core particle and a conductive layer having a plurality of protrusions on the surface of the core particle, wherein when the cross sections of 20 conductive particles are observed under an SEM and the heights of all the protrusions of each conductive particle are measured, the variation in height of the protrusions calculated from the following calculation formula (1) is 0.01 or more and 0.25 or less. [0010]
2. The conductive particle according to claim 1 , wherein the top portions of the protrusions are substantially flat.
3. 2. The conductive particle according to claim 1, wherein the ratio of Ra to Rb (Ra / Rb) is 0.15 or more and 1.20 or less, where Ra is the radius of curvature of the top portion of the protrusion and Rb is the radius of curvature of the surface of the lower layer of the conductive layer at the portion where the protrusion is formed.
4. 2. The conductive particle according to claim 1, wherein a ratio of a total area of the top portions of said protrusions to a projected area of said conductive particle is 0.50 or more.
5. 2. The conductive particle according to claim 1, wherein the conductive layer contains at least one selected from the group consisting of nickel, gold, and palladium.
6. 2. The conductive particles according to claim 1, having an average particle size of 0.1 μm or more and 50 μm or less.
7. The conductive particle according to claim 1 , wherein the conductive layer has a thickness of 0.1 nm or more and 2,000 nm or less.
8. The conductive particle according to claim 1 , wherein the height of the protrusions is from 20 nm to 1,000 nm.
9. The conductive particle according to claim 1 , wherein at least one of the protrusions has an irregular shape.
10. A conductive material comprising the conductive particles according to claim 1 and an insulating resin.
11. A step of forming a conductive layer on the surface of the core particles; forming a protrusion on the conductive layer so as to protrude from the surface; and A step of leveling the height of the protrusions The method for producing conductive particles according to claim 1 , comprising the steps of:
12. The method for producing conductive particles according to claim 11, wherein the step of forming the protrusions comprises forming the protrusions on the conductive layer using autolyzed products of the electroless nickel plating bath as nuclei.
13. The method for producing conductive particles according to claim 11 or 12, wherein the step of leveling the height of the protrusions comprises polishing the top portions of the protrusions obtained in the step of forming the protrusions to level the height of the protrusions.